Comparative Environmental Impacts of Chemical, Organic, and Integrated Fertilizer Use on Soil Quality, Water Resources, Greenhouse Gas Emissions, and Crop Productivity - SABIU , Abdulaziz; ITAMAH, Ehime; SANI, Aliyu (ABUAD Journal of Engineering and Applied Sciences, 2025)
The environmental footprint of fertiliser use in agriculture poses critical concerns amid efforts toward sustainable food production. This study evaluated the comparative effects of chemical (NPK 15:15:15), organic (poultry manure), and integrated (50:50 chemical–organic) fertilisers on soil physicochemical properties, water quality, greenhouse gas emissions, soil enzymatic and microbial activity, crop yield, and nutrient use efficiency (NUE) under maize (Zea mays L.) cultivation in the Guinea Savanna zone of Lokoja, Nigeria. A two-season field experiment was conducted using a randomised complete block design (RCBD) with replicated plots; standard laboratory and chromatographic techniques were employed to analyse soil (pH, organic carbon, nutrient content, microbial biomass, enzymes), water runoff nutrient concentrations, and GHG fluxes (CO₂, CH₄, N₂O) via static chambers. Results showed that organic fertiliser (T2) significantly improved soil health (organic carbon 2.46%, pH 6.8, microbial biomass 413 mg C/kg) and enzyme activity, while reducing nutrient leaching and greenhouse gas emissions. The integrated treatment (T3) achieved the highest total nitrogen (0.23%), maize yield (3.42 t/ha), biomass (6.34 t/ha), and NUE (N: 58.7%, P: 49.5%, K: 61.3%). Sole chemical fertiliser (T1) had poorer soil biological indicators and the highest nitrate (32.4 mg/L) and N₂O emissions (2.14 mg N₂O‑N m⁻² h⁻¹). Overall, integrated fertilisation offers an optimal balance between productivity and environmental protection. These findings support the adoption of integrated nutrient management in tropical systems to enhance soil health, reduce pollution and GHG emissions, and boost crop yields cost-effectively—a strategy relevant for farmers, extension services, and policymakers.